Preparation of acetate peels of valves from the ocean quahog, Arctica islandica, for age determinations - Ropes, John W. (NOAA/National Marine Fisheries Service, 1987)
Techniques are described for preparing acetate peels of sectioned valves of ocean quahogs, Arctica islandica, for age determinations. The respective sequence of preparation begins by sectioning left valves oriented to include a single hinge tooth, bleaching to remove the heavy periostracum, embedding the valves in an epoxy resin, grinding and polishing the embedments to a high luster, etching the exposed cut valve surfaces, and applying sheet acetate with acetone. Annuli are clearly defined relative to growth increments in the peel preparations for all sizes and ages of ocean quahogs. (PDF file contains12 pages.)